Review Artikel : Pengaruh Terapi Obat Anti Epilepsi (OAE) Terhadap Ibu Hamil Pengidap Epilepsi - Fajar Adi Prasetya; Ali Alfarizzy; Muhamad Al Atoriq; Maya Arfania (Peneliti.net, 2023)
Epilepsy is a brain disorder characterized by a persistent predisposition to experience seizures and has neurobiological, cognitive, psychological, and social consequences. Pregnancy in women with epilepsy is still considered a high-risk pregnancy. The use of anti-epileptic drugs (OAE) in pregnant women is not completely safe and given freely. This is because Anti-Epilepsy Drugs (OAE) have side effects for the fetus they contain. The effect of anti-epileptic drug therapy (OAE) in pregnant women can result in developmental delays in the fetus and baby, defects, facial abnormalities, congenital heart defects, nail hypoplasia, learning disabilities and mental retardation.